2018
DOI: 10.3892/ol.2018.8595
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑154 functions as a tumor suppressor in non‑small cell lung cancer through directly targeting B‑cell‑specific Moloney murine leukemia virus insertion site 1

Abstract: Abstract. Lung cancer remains the leading cause of cancer-associated mortality in China and worldwide. Increasing numbers of studies have demonstrated that microRNAs (miRNAs/miRs) have vital functions in numerous developmental processes and tumorigenesis. The aim of the present study was to investigate miR-154 expression in non-small cell lung cancer (NSCLC), and to explore the roles of miR-154 in the carcinogenesis and progression of this cancer. Reverse transcription-polymerase chain reaction (RT-qPCR) was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In another study by Xu et al, E2F transcription factor 5 protein (E2F5) was introduced as a direct target of miR-154, with reciprocal relationship between these two parameters in in neoplastic cells of breast [14]. Additionally, reduced levels of miR-154 and its association with aggressive clinicopathological characteristics have been reported in glioma, colorectal, prostate and non-small cell lung cancers [2427].…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Xu et al, E2F transcription factor 5 protein (E2F5) was introduced as a direct target of miR-154, with reciprocal relationship between these two parameters in in neoplastic cells of breast [14]. Additionally, reduced levels of miR-154 and its association with aggressive clinicopathological characteristics have been reported in glioma, colorectal, prostate and non-small cell lung cancers [2427].…”
Section: Discussionmentioning
confidence: 99%
“…None of the controls significantly affected the luciferase activity. Additionally, reduced levels of miR-154 and its association with aggressive clinicopathological carachteristics have also been reported in glioma, colorectal, prostate and non-small cell lung cancers (23)(24)(25)(26)).…”
Section: Mir-154 Regulated Nampt By Direct Binding To Its 3′-utrmentioning
confidence: 86%
“…For example, miR-154 functions as a tumor suppressor in non-small cell lung cancer by directly targeting BMI-1. 42 Xu et al reported that miR-154 inhibits the growth and invasion of breast cancer cells by targeting E2F5. 43 It was also reported that ZEB2 and RUNX2 act as targets of miR-154 in non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%